الإستشراف : الرؤية المستقبلية - بازمول، محمد بن عمر بن سالم (جامعة أم القرى, 2011)
النفوس تتشوف إلى ما غاب عنها، ولأجل ذلك توضع الدراسات المستقبلية للمشاريع الدنيوية والدينية الدعوية، فهل يجوز ذلك؟ وما هو تعريف الاستشراف ؟ وما أنوعه؟ وما أدواته؟ وما حكمه؟ وما ضوابطه؟ وهل في الاستشراف ما ينافي التوكل؟ هل فيه ما يتنافى مع الزهد؟ هل فيه معارضة مع الإيمان بقضاء الله وقدره؟ هل فيه ركون إلى الدنيا واشتغال بها عن الآخرة؟ \ وقد أجابت الدراسة عن هذه الأسئلة، وانتهت إلى أن الاستشراف (الرؤية المستقبلية) من الأمور التي أقرها الشرع، ولا مانع منها بشرط أن يتم بما لا يخالف الشرع، فالاستشراف في أمور الحياة بالأمور العادية، من الأمور السائغة والاستشراف الذي يقوم على معطيات من الخبر الغيبي الشرعي، مباح كذلك، بل قد يكون واجباً أو مستحباً. مع مراعاة الضوابط التي دلت عليها الأدلة الشرعية، ليتجنب المسلم إذا ما أراد تكوين رؤية مستقبلية الوقوع في ما يخالف الشرع. Because of basic human curiosity, studies about long-term future planning for both secular and religious spheres of life are planned. Are these studies allowed in Islam? What is the working definition of istishraf (futurology)? What are its branches? What are its essential tools? What is the wisdom behind it? What are its acceptable limits? Is futurology something that negates the Islamic concept of tawakkul (trusting completely in Allah)? Does it entail too much focus on this worldly life? Does it violate the Islamic belief system of divine pre-ordainment (Qadr)? Is it a kind of infatuation with this wordly life that requires neglect of the affairs of the Hereafter? \ This study answers all of these questions. It concludes that futurology is supported by Islam (in general), so long as it does not include any ideas that violate established Islamic regulations. Thus, futurology applied to routine life situations is acceptable. \ Futurology based on established predictions from divine revelation is also permissible, or possibly even recommended or obligatory in some cases, while observing the limits and guidelines laid down in the divine texts of revelation, so that Muslims can plan their future in a way that helps them avoid violations of their religion
Keywords: الشريعة الإسلامية -- الإستشراف -- التوقعات المستقبلية -- التوكل -- الزهد -- الإيمان بالقضاء و القدر -- الأحكام الشرعية -- حكم الإستشراف